Potensi Spirulina platensis sebagai sumber kosmetik dan bioplastik (review) - Tutik Muji Setyoningrum; Halim Nur Aziz Suwardi; Bety Alfitamara; Adi Kurniawan; Vinka Azzah Prananda; Dwi Nur Afni; Sheila Alodia; Retno Pamularsih; Muhamad Maulana Azimatun Nur (Eksergi, 2021)
Spirulina plantesis is a cyanobacteria that has many purposes such as for cosmetics, and food industry. In addition, Spirulina platensis can accumulate polyhydroxybutyrate (PHB), a type of bioplastic. This review discussed the potency of Spirulina platensis as a source of bioplastics and cosmetics. From the review, Spirulina contained bioactive compound, C-phycocyanin, which can inhibit cell damage and is very potential to be applied for cosmetics. The PHB content in Spirulina tends to be small compared to other microalgae. To reduce the cost of PHB from Spirulina, the biorefinery concept can be applied, by recovery the bioactive components (C-phycocyanin), while the residue can be used as a source of PHB.